PERAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI DALAM MEMODERASI PENGARUH KOMPETENSI GURU TERHADAP KEPUASAN KERJA GURU DI SMA NEGERI DI KABUPATEN PATI - Suhartono, 11.52.02.0043 (Students Journal of Economic and Management, 2013)
Influence ofteacher competence onteacherjob satisfactionis influencedbypossibleother variables, bothmediatingandmoderatingvariables. Moderating variablesto be observedin this studyisthe ability ofthe principalmanagerialand organizational culture. The sample inthis study were204teachers fromeighthigh schools inPatianddata analysisusingregressionanalysis. The resultis asignificant effect on thecompetence ofthe teacherjob satisfactionmeans the betterthe competency ofa teacher, it will increase job satisfactionof teachers. The ability ofthe principalmanagerialsignificant negative effectinmoderatingthe influence ofteacher competence onjob satisfaction.Weaken the influence oforganizational cultureon job satisfaction ofteachers competence. Keywords : TeacherCompetence, ManagerialAbilityPrincipal, Organizational CultureandJob Satisfaction